DESAIN MESIN SPINNER BERBASIS IoT - Lis Diana Mustafa; Hadiwiyatno; Yani Ratnawati (LPPM Politeknik Jambi, 2019)
At present a lot off snack is produced by small industries that use oil-based ingredients for frying, fried snacks have a limitation of less consumption age because there is oil content in it Therefore an oil draining machine is made which functions to drain the oil but can be operated using a smartphone device. This drain machine is equipped with the MCU ESP32 node which is connected to firebase via the internet. The software used to design this is Android Studio.The results of this system are as planned. This is evidenced by the data displayed on Firebase same as Android applications. There are 2 modes, namely automatic and manual modes that can be selected by the user to operate this spinner.